Ethnic minority children's and adults' perceptions and experiences of schooling in Vietnam: A case study of the Cham H'Roi - Vu, T (Palgrave Macmillan UK, 2014)
The development of productive capacities or ‘skills’ is the key mechanism through which education acquires economic value, for both individuals and society; and the imperative to ‘upskill’ the labour force finds plentiful expression in the rhetoric of education and development policy at both the country and international levels, often linked to concerns around globalization and increasing competition. Improvements in access to formal education in many developing countries since the turn of the millennium have meant that youth populations in these countries are more likely than their forebears to enrol in school and to stay there longer. Rapidly rising levels of educational access have nonetheless highlighted issues of educational quality and relevance in the face of global financial uncertainty and constrained national budgets and in the context of an expanding youth population. Educational advancement remains an important driver of social mobility and may serve to reduce the intergenerational transmission of poverty, especially where it provides access to economic opportunity.